Insulation material and a device for drying clothing containing moisture.

JP2026170785APending Publication Date: 2026-10-22ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025064577
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-22

AI Technical Summary

Benefits of technology

【0017】 本開示によれば、洗濯乾燥機等の衣類を乾燥させる装置に適用できる断熱材を提供できる。 本開示によれば、かかる断熱材を配した水分を含む衣類を乾燥させる装置を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026170785000001
    Figure 2026170785000001
  • Figure 2026170785000002
    Figure 2026170785000002
  • Figure 2026170785000003
    Figure 2026170785000003
Patent Text Reader

Abstract

The objective is to provide an insulating material that can be applied to clothing drying devices such as washing machines and dryers. [Solution] The resin foam (A) contains resin (a), and the resin foam (A) has a flame retardancy of V-0 to V-2 as measured in accordance with the UL standard UL-94 vertical method (20 mm vertical combustion test), and the resin foam (A) has a water absorption rate of 0.01 g / cm³ as measured in accordance with JIS K6767B. 2 The following is a thermal insulation material used in a device for drying clothes containing moisture, wherein the glass transition temperature of the resin (a) contained in the resin foam (A) is 90°C or higher.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to thermal insulation materials and apparatus for drying clothing containing moisture. [Background technology]

[0002] Traditionally, insulation materials have been used in buildings and various heat-utilizing devices to prevent heat loss and other purposes. The material of the insulation applied to these applications is selected according to the required properties.

[0003] For example, Patent Document 1 below discloses a foamed plastic-based thermal insulation material characterized in that a ceramic thermal insulation layer formed by applying a ceramic coating is provided on the surface of a sheet-like material laminated on at least one of the front and back surfaces of a plastic-based foam. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2010-110978 [Overview of the project] [Problems that the invention aims to solve]

[0005] In recent years, washer-dryers and dryers have been used to dry clothes after washing. Since these devices use heat to dry clothes, it is desirable to minimize heat loss from an efficiency standpoint. One possible solution is to install insulation in washing machines and dryers. However, conventionally, there has been no insulation material suitable for use in washing machines and dryers.

[0006] Therefore, the objective of this disclosure is to solve the problems of the above-mentioned prior art and to provide an insulating material that can be applied to clothing drying devices such as washing machines and dryers. A further problem of the present disclosure is to provide an apparatus for drying moisture-containing clothing provided with such a heat insulating material. [MEANS FOR SOLVING THE PROBLEMS]

[0007] As a result of intensive investigations aimed at solving the above problems, the present inventors have found that the above problems can be solved by a heat insulating material comprising a resin foam (A) that satisfies predetermined physical properties, and have completed the present invention. The essential configuration of the present disclosure for solving the above problems is as follows.

[0008] [1] A heat insulating material comprising a resin foam (A) containing a resin (a), wherein the resin foam (A) has a flame retardancy of V-0 to V-2 as measured in accordance with the UL-94 vertical method (20 mm vertical burning test) of UL standards, the resin foam (A) has a water absorption rate measured in accordance with JIS K6767B of 0.01 g / cm 2 or less, the resin (a) contained in the resin foam (A) has a glass transition temperature of 90°C or higher, and the heat insulating material is for use in an apparatus for drying moisture-containing clothing.

[0009] [2] The heat insulating material according to [1], wherein the resin foam (A) comprises a bead foam.

[0010] [3] The heat insulating material according to [1] or [2], wherein the resin foam (A) has a closed cell ratio of 75% or more.

[0011] [4] The heat insulating material according to any one of [1] to [3], wherein the resin foam (A) has a density of 0.01 g / cm 3 to 0.400 g / cm 3 or less.

[0012] [5] The heat insulating material according to any one of [1] to [4], further comprising a non-flame-retardant foam (B).

[0013] [6] The resin (a) contained in the resin foam (A) includes a polystyrene resin, The thermal insulation material according to any one of [1] to [5], wherein the content of styrene monomer units is 8.0% by mass or more and 70.0% by mass or less in the resin foam (A).

[0014] [7] The insulating material according to any one of [1] to [6], wherein the device for drying the clothes containing moisture is a drum-type washing machine and dryer.

[0015] [8] The thermal insulation material according to any one of [1] to [7], wherein the resin (a) contained in the resin foam (A) contains a polyphenylene ether resin.

[0016] [9] A device for drying clothes containing moisture, equipped with an insulating material as described in any of [1] to [8]. [Effects of the Invention]

[0017] According to this disclosure, it is possible to provide an insulating material that can be applied to clothing drying devices such as washing machines and dryers. According to this disclosure, an apparatus for drying clothes containing moisture, which are fitted with such insulating material, can be provided. [Modes for carrying out the invention]

[0018] The thermal insulation material and apparatus for drying clothing containing moisture described herein will be explained in detail below based on their embodiments.

[0019] <Insulation material> The thermal insulation material of this embodiment is The resin foam (A) contains resin (a), The aforementioned resin foam (A) has a flame retardancy of V-0 to V-2 as measured in accordance with the UL standard UL-94 vertical method (20 mm vertical combustion test). The aforementioned resin foam (A) has a water absorption rate of 0.01 g / cm³ as measured in accordance with JIS K6767B. 2 The following: The glass transition temperature of the resin (a) contained in the resin foam (A) is 90°C or higher. It is characterized by being used in a device for drying clothes that contain moisture. The above-mentioned insulation material possesses the necessary physical properties for application to clothing drying equipment such as washing machines and dryers, and therefore can be applied to such equipment.

[0020] The thermal insulation material of this embodiment is used in a device for drying clothes containing moisture. In this specification, "device for drying clothes containing moisture" includes, for example, a washer-dryer and a dryer. Washer-dryers include drum-type washer-dryers and top-loading washer-dryers. In other words, the thermal insulation material of this embodiment is a thermal insulation material for a device for drying clothes containing moisture, and more specifically, a thermal insulation material for a washer-dryer, and even more specifically, a thermal insulation material for a drum-type washing machine. Traditionally, appliances that dry clothes containing moisture, such as washer-dryers, have not been equipped with insulation. Since washer-dryers not only dry clothes but also wash them, the insulation used in them must be water-resistant. Furthermore, because heat is used to dry clothes, the insulation must be not only water-resistant but also heat-resistant and flame-retardant. However, conventionally, no insulation material existed that fully satisfied all of these requirements. Therefore, it is believed that washer-dryers traditionally lacked insulation. In contrast, the thermal insulation material of this embodiment has excellent water resistance, heat resistance, and flame retardancy, making it applicable to equipment for drying clothes containing moisture. By applying the thermal insulation material of this embodiment to equipment for drying clothes containing moisture, it is possible to prevent heat from escaping during the drying process. This makes it more difficult for the heat used for drying to escape. As a result, drying time can be shortened, and it is also believed that this will contribute to sustainability by reducing energy consumption, lowering electricity costs, and reducing CO2 emissions.

[0021] The shape and size of the insulating material in this embodiment can be arbitrarily set to match the shape of the device used to dry the moisture-containing clothing. The shape and size of the insulating material can be appropriately selected depending on the shape and size of the mold used to manufacture the insulating material.

[0022] The thermal insulation material of this embodiment includes a resin foam (A). Alternatively, the thermal insulation material of this embodiment may consist solely of the resin foam (A), or it may include, in addition to the resin foam (A), other foams (hereinafter simply referred to as "other foams"). The resin foam (A) and the other foams will be described later.

[0023] (Resin foam (A)) The resin foam (A) exhibits excellent flame retardancy, with a flame retardancy of V-0 to V-2 as measured according to the UL standard UL-94 vertical method (20mm vertical combustion test). Furthermore, the resin foam (A) has a water absorption rate of 0.01 g / cm³ as measured according to JIS K6767B. 2 Because of the following, it has excellent water resistance. Furthermore, the resin foam (A) has excellent heat resistance because the glass transition temperature of the resin (a) contained in the resin foam (A) is 90°C or higher. The heat insulating material of this embodiment contains such a resin foam (A) which has excellent flame retardancy, water resistance, and heat resistance, and is therefore excellent in flame retardancy, water resistance, and heat resistance, and can be applied to equipment for drying clothes containing moisture that requires these properties.

[0024] The resin foam (A) may include bead foam. Preferably, the resin foam (A) consists of bead foam. Bead foam has excellent shapeability and can be processed into fine and complex shapes.

[0025] The bead foam is obtained by foaming foam beads. The foam beads are obtained by pre-foaming a base resin. The foam beads have the same components as the bead foam (i.e., resin foam (A)). The base resin also contains the same components as resin foam (A) (foam beads and bead foam), except for the foaming agent described later.

[0026] [Expanded Beads] Expanded beads are produced by adding a blowing agent to a base resin containing the components constituting the expanded beads and performing pre-expansion. By expanding the expanded beads, a bead foam can be molded.

[0027] The expanded beads preferably have an average particle diameter of 0.5 to 10 mm, more preferably 0.7 to 5 mm. When the average particle diameter of the expanded beads is 0.5 to 10 mm, molding of a bead foam having a complex and fine shape becomes even easier.

[0028] The density of the expanded beads is preferably 0.01 to 0.80 g / cm 3 , more preferably 0.04 to 0.67 g / cm 3 , even more preferably 0.05 to 0.5 g / cm 3 , still more preferably 0.06 to 0.4 g / cm 3 , further preferably 0.07 to 0.3 g / cm 3 , and particularly preferable. When the density of the expanded beads is 0.01 to 0.80 g / cm 3 , expanded beads that are easy to subject to the secondary expansion step are easily obtained, and by setting the density particularly in the range of 0.06 to 0.4 g / cm 3 , it becomes even easier to satisfy desired flame retardancy.

[0029] The closed cell ratio of the expanded beads is preferably as high as possible, and is 50% or more, preferably 60% or more, more preferably 70% or more, even more preferably 73% or more, still more preferably 76% or more, and particularly preferably 79% or more. When the closed cell ratio of the expanded beads is 50% or more, the expanded beads tend to have more excellent molding processability into a bead foam, and when the closed cell ratio is 70% or more, the expanded beads tend to have excellent heat insulating properties.

[0030] [Composition of Resin Foam (A)] First, the composition of the resin foam (A) will be described.

[0031] -Resin (a)- The resin foam (A) contains resin (a). Resin (a) may include thermoplastic resins and / or thermosetting resins. Resin (a) may be a single type or a combination of two or more types.

[0032] Examples of thermoplastic resins include polyolefin resins such as polyethylene, polypropylene, and EVA (ethylene-vinyl acetate copolymer), polyvinyl alcohol, polyvinyl chloride, polyvinylidene chloride, ABS (acrylonitrile-butadiene-styrene) resin, AS (acrylonitrile-styrene) resin, polystyrene resin, methacrylic resin, polyamide resin, polycarbonate resin, polyphenylene ether resin, polyimide resin, polyacetal resin, polyester resin, acrylic resin, cellulose resin, styrene-based, polyvinyl chloride-based, polyurethane-based, polyester-based, polyamide-based, 1,2-polybutadiene-based, fluororubber-based thermoplastic elastomers, polyamide-based, polyacetal-based, polyester-based, fluororubber-based thermoplastic engineering plastics, and powdered rubber. These may be used individually or in combination. Furthermore, modified, copolymerized, compounded, or crosslinked resins may be used, as long as they do not impair the objectives of the present invention.

[0033] Examples of thermosetting resins include phenolic resins, urea resins, amino resins such as melamine resins, unsaturated polyester resins, and epoxy resins.

[0034] Among these, polyphenylene ether resins or polycarbonate resins are preferred in terms of improving flame retardancy, and polyphenylene ether resins are more preferred. In other words, the resin preferably contains a polyphenylene ether resin or a polycarbonate resin, and more preferably contains a polyphenylene ether resin.

[0035] --Polycarbonate resin-- The polycarbonate resin is preferably a carbonate ester resin derived from bisphenols and phosgene (or diphenyl carbonate), and is characterized by having a high glass transition temperature and heat resistance. Suitable polycarbonates for this purpose include, for example, polycarbonates derived from 2,2'-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2'-bis(4-hydroxyphenyl)butane (bisphenol B), 1,1'-bis(4-hydroxyphenyl)ethane, bis(4-hydroxyphenyl)methane (bisphenol F), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)-1-phenylmethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,2-bis(4-hydroxyphenyl)ethane, etc. These polycarbonate resins generally have a glass transition temperature (Tg) of 140 to 155°C. By using resins with such a glass transition temperature as the resin constituting the thermal insulation material, it is possible to create a thermal insulation material with excellent heat resistance.

[0036] In this specification, polycarbonate resins can be mixed with one or more other resins, examples of which include polyethylene resins, polypropylene resins, acrylonitrile-butadiene-styrene copolymers (ABS resins), polystyrene resins, polyethylene terephthalate, polybutylene terephthalate, acrylonitrile-styrene copolymers (AS resins), syndiotactic polystyrene, polyphenylene oxide, polyacetal, polymethyl methacrylate, polyphenylene sulfide, polyethersulfone, polyarylate, polyamide, polyimide, or polyethylene naphthalate. When mixing polycarbonate resin with other resins, from the viewpoint of flame retardancy, the polycarbonate resin content is preferably 50% by mass or more, and more preferably 70% by mass or more.

[0037] --Polyphenylene ether resin-- In this specification, polyphenylene ether resin refers to a polymer represented by the following general formula (1). [ka] Here, in the general formula (1) above, R 1 , R 2 , R 3 and R 4 Each of these independently represents hydrogen, halogen, alkyl group, alkoxy group, phenyl group, or a haloalkyl group or haloalkoxy group having at least two carbon atoms between the halogen and the benzene ring in general formula (1), and not containing a third α-carbon. Also, n is an integer representing the degree of polymerization.

[0038] The polyphenylene ether resin is preferably one with a weight-average molecular weight of 10,000 to 70,000. More preferably, the weight-average molecular weight of the polyphenylene ether resin is in the range of 15,000 to 60,000, and even more preferably 20,000 to 55,000. In this specification, the weight-average molecular weight is the weight-average molecular weight obtained by measuring with gel permeation chromatography (GPC) and using a calibration curve (created using the peak molecular weight of standard polystyrene) obtained from measurements of commercially available standard polystyrene.

[0039] Examples of polyphenylene ether resins include poly(2,6-dimethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene) ether, poly(2-methyl-6-ethyl-1,4-phenylene) ether, poly(2-methyl-6-propyl-1,4-phenylene) ether, poly(2,6-dipropyl-1,4-phenylene) ether, poly(2-ethyl-6-propyl-1,4-phenylene) ether, poly(2,6-dibutyl-1,4-phenylene) ether, poly(2,6-dilauryl-1,4-phenylene) ether, poly(2,6-diphenyl-1,4-diphenylene) ether, and poly(2,6-dimethoxy-1 Examples include, but are not limited to, ,4-phenylene) ether, poly(2,6-diethoxy-1,4-phenylene) ether, poly(2-methoxy-6-ethoxy-1,4-phenylene) ether, poly(2-ethyl-6-stearyloxy-1,4-phenylene) ether, poly(2,6-dichloro-1,4-phenylene) ether, poly(2-methyl-6-phenyl-1,4-phenylene) ether, poly(2,6-dibenzyl-1,4-phenylene) ether, poly(2-ethoxy-1,4-phenylene) ether, poly(2-chloro-1,4-phenylene) ether, and poly(2,6-dibromo-1,4-phenylene) ether. These polyphenylene ether resins generally have a glass transition temperature (Tg) of 110 to 230°C. By using a polyphenylene ether-based resin having such a glass transition temperature as the resin constituting the thermal insulation material, a thermal insulation material with excellent heat resistance can be obtained.

[0040] Among these, R 1 and R 2 is an alkyl group having 1 to 4 carbon atoms, and R 3 and R 4 Polyphenylene ether resins in which the element is hydrogen or an alkyl group having 1 to 4 carbon atoms are preferred. These may be used individually or in combination of two or more.

[0041] When resin (a) contains a polyphenylene ether resin, the polyphenylene ether resin content is preferably 21% by mass or more in the resin foam (A). If the polyphenylene ether resin content is 21% by mass or more, the heat resistance is excellent, and furthermore, the flame retardancy, in particular the performance of preventing resin dripping during combustion is significantly improved. In order to prevent resin dripping during combustion, it is important to (1) shorten the burning time and (2) increase the heat resistance of the resin (make it less likely to soften). However, simply increasing the amount of flame retardant added has the opposite effect on (2), and in order to prevent resin dripping in thinner samples, it is preferable to have a polyphenylene ether resin content of 31% by mass or more. From a similar viewpoint, the polyphenylene ether resin content is more preferably 36% by mass or more in the resin foam (A), even more preferably 44% by mass or more, even more preferably 48% by mass or more, and particularly preferably 52% by mass or more. On the other hand, the content of polyphenylene ether resin is preferably 94% by mass or less in the resin foam (A). If the content of polyphenylene ether resin exceeds 94% by mass, the temperature required for processing such as foaming and molding rises sharply, which not only increases utility costs but also necessitates special equipment, resulting in poor actual productivity. The content of polyphenylene ether resin is more preferably 90% by mass or less in the resin foam (A), even more preferably 84% by mass or less, even more preferably 80% by mass or less, even more preferably 76% by mass or less, even more preferably 72% by mass or less, even more preferably 68% by mass or less, and even more preferably 64% by mass or less. In particular, the content of polyphenylene ether resin is preferably in the range of 21% by mass or more and 68% by mass or less in the resin foam (A). By keeping it within this range, a resin foam (A) with an excellent balance of heat resistance, foamability, and flame retardancy can be obtained.

[0042] Polyphenylene ether resins can be mixed with one or more other resins, including polystyrene resins, polyolefin resins such as polypropylene, aliphatic polyamide resins, aromatic polyamide resins, engineering plastics such as polybutylene terephthalate resins, and super engineering plastics such as polyphenylene sulfide. Among these, mixing with polystyrene resins, which have excellent compatibility with polyphenylene ether, is preferable from the viewpoint of improving processability.

[0043] As described above, it is particularly preferable that resin (a) is a mixture of a polyphenylene ether resin and a polystyrene resin, but it is not limited to this, and the polystyrene resin does not have to be mixed with the polyphenylene ether resin. That is, resin (a) may include a styrene resin that is not mixed with other resins. In one preferred embodiment, resin (a) includes a polyphenylene ether resin and a styrene resin.

[0044] --Polystyrene resin-- In this specification, polystyrene resins refer to homopolymers of styrene and styrene derivatives, as well as copolymers mainly composed of styrene and styrene derivatives. Examples of styrene derivatives include, but are not limited to, o-methylstyrene, m-methylstyrene, p-methylstyrene, t-butylstyrene, α-methylstyrene, β-methylstyrene, diphenylethylene, chlorostyrene, and bromostyrene.

[0045] Examples of homopolymer polystyrene resins include polystyrene, poly-α-methylstyrene, and polychlorostyrene. Examples of copolymer polystyrene resins include styrene-butadiene copolymer, styrene-acrylonitrile copolymer, styrene-maleic acid copolymer, styrene-maleic anhydride copolymer, styrene-maleimide copolymer, styrene-N-phenylmaleimide copolymer, styrene-N-alkylmaleimide copolymer, styrene-N-alkyl-substituted phenylmaleimide copolymer, styrene-acrylic acid copolymer, styrene-methacrylic acid copolymer, styrene-methacrylic acid-methyl methacrylate copolymer, styrene-methyl acrylate copolymer, styrene-n-alkyl acrylate copolymer, styrene-n-alkyl methacrylate copolymer, and ethyl vinylbenzene-divinylbenzene copolymer, as well as ternary copolymers such as ABS and butadiene-acrylonitrile-α-methylbenzene copolymer. However, polystyrene resins are not limited to these.

[0046] When a copolymer polystyrene resin is mixed with the polyphenylene ether resin, the content of copolymer monomers other than styrene and styrene derivatives is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 8% by mass or less, even more preferably 6% by mass or less, and particularly preferably 5% by mass or less in the copolymer polystyrene resin. In particular, by setting the content of copolymer monomers other than styrene and styrene derivatives to 5% by mass or less in the copolymer polystyrene resin, excellent compatibility with the polyphenylene ether resin is achieved.

[0047] Furthermore, polystyrene resins also include graft copolymers, such as styrene-grafted polyethylene, styrene-grafted ethylene-vinyl acetate copolymer, (styrene-acrylic acid)-grafted polyethylene, and styrene-grafted polyamide. These may be used individually or in combination of two or more.

[0048] The polystyrene resin is preferably one with a weight-average molecular weight of 100,000 to 500,000. More preferably, the weight-average molecular weight of the polystyrene resin is in the range of 150,000 to 400,000, even more preferably 180,000 to 370,000, and still more preferably 200,000 to 350,000. In this specification, the weight-average molecular weight is the weight-average molecular weight obtained by measuring with gel permeation chromatography (GPC) and using a calibration curve (created using the peak molecular weight of standard polystyrene) obtained from measurements of commercially available standard polystyrene.

[0049] From the viewpoint of imparting foam moldability, the polystyrene resin content is preferably 7.0% by mass or more and 70.0% by mass or less in the resin foam (A). Similarly, the polystyrene resin content is more preferably 8.0% by mass or more and 66% by mass or less in the resin foam (A), and even more preferably 9% by mass or more and 62% by mass or less.

[0050] [Physical properties of resin (a)] The resin (a) contained in the resin foam (A) has a glass transition temperature of 90°C or higher. A glass transition temperature of 90°C or higher for resin (a) makes it a heat-insulating material with excellent heat resistance. From the viewpoint of excellent heat resistance, the glass transition temperature of resin (a) is preferably 100°C or higher, more preferably 110°C or higher, even more preferably 120°C or higher, and even more preferably 130°C or higher. On the other hand, the glass transition temperature of resin (a) may be 180°C or lower. In devices for drying clothes containing moisture, the maximum temperature in a large gas dryer is around 150°C; therefore, if the temperature is below the above upper limit, it will be a heat-insulating material with sufficient heat resistance for application in devices for drying clothes containing moisture. The glass transition temperature of resin (a) is the peak temperature of the loss tangent (tanδ) peak obtained by dynamic viscoelasticity measurement, and is the value measured by the method described in the examples below.

[0051] -Flame retardant- The resin foam (A) preferably contains a flame retardant to achieve sufficient flame retardancy. Flame retardants include organic flame retardants and inorganic flame retardants. Organic flame retardants include halogen compounds represented by bromine compounds, and non-halogen compounds represented by phosphorus compounds and silicone compounds. Inorganic flame retardants include metal hydroxides represented by aluminum hydroxide and magnesium hydroxide, antimony compounds represented by antimony trioxide and antimony pentoxide.

[0052] Among the above-mentioned flame retardants, non-halogen-based flame retardants are preferred from an environmental standpoint, and phosphorus-based and silicone-based flame retardants are more preferred, but the system is not limited to these.

[0053] Phosphorus-based flame retardants can include those containing phosphorus or phosphorus compounds. Red phosphorus is an example of phosphorus. Examples of phosphorus compounds include phosphate esters and phosphazene compounds having a phosphorus-nitrogen bond in the main chain. Examples of phosphate esters include trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tripentyl phosphate, trihexyl phosphate, tricyclohexyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, cresyl diphenyl phosphate, dicresyl phenyl phosphate, dimethyl ethyl phosphate, methyl dibutyl phosphate, ethyl dipropyl phosphate, hydroxyphenyl diphenyl phosphate, resorcinol bis-diphenyl phosphate, and others. Compounds modified with various substituents and various condensation-type phosphate ester compounds are also included. Among these, triphenyl phosphate and phosphate ester compounds represented by the following general formula (2) are preferred from the viewpoint of heat resistance, flame retardancy, and foaming properties.

[0054] [ka] Here, in the above general formula (2), Q 1 ~Q 8Each of these independently represents hydrogen, halogen, alkyl group, alkoxy group, or phenyl group. Q in general formula (2) 1 ~Q 4 The preferred group is hydrogen or a methyl group. Q in general formula (2) 5 , and Q 6 The preferred element is hydrogen, Q 7 , and Q 8 A methyl group is preferred. In general formula (2), m is an integer of 1 or more. The phosphate ester compound may be a mixture of m-mers. In general formula (2), n1 to n4 are each independently integers from 1 to 5, and n5 and n6 are each independently integers from 1 to 4.

[0055] Furthermore, (mono or poly)organosiloxanes can be used as silicone-based flame retardants. Examples of (mono or poly)organosiloxanes include monoorganosiloxanes such as dimethylsiloxane and phenylmethylsiloxane, and organopolysiloxanes such as polydimethylsiloxane, polyphenylmethylsiloxane, and copolymers thereof obtained by polymerizing these. In the case of organopolysiloxanes, the bonding groups of the main chain and branched side chains are hydrogen, alkyl, or phenyl groups, preferably phenyl, methyl, ethyl, and propyl groups, but not limited to these. Terminal bonding groups can be hydroxyl, alkoxy, alkyl, or phenyl groups. There are no particular restrictions on the shape of the silicones, and any form such as oil, gum, varnish, powder, or pellets can be used.

[0056] Furthermore, various conventionally known flame retardants and flame retardant additives, such as cyclic nitrogen compounds, specifically compounds having a triazine skeleton such as melamine, ammerido, ammerine, benzoguanamine, succinoguanamine, melamine cyanurate, melam, merem, meton, melon, and their sulfates, alkali metal hydroxides or alkaline earth metal hydroxides such as magnesium hydroxide or aluminum hydroxide containing water of crystallization, zinc borate compounds, zinc stannate compounds, etc., may also be used. Moreover, these may be included not just individually, but in combination of multiple types.

[0057] The flame retardant content is preferably 5 to 23% by mass of the resin foam (A), more preferably 7 to 20% by mass, and even more preferably 9 to 17% by mass. When the flame retardant content is 5% by mass or more, the desired flame retardancy is more easily achieved. Conversely, when the flame retardant content is 20% by mass or less, the plasticizing effect of the flame retardant on the resin (a) becomes appropriate, improving heat resistance. Furthermore, the extensional viscosity of the resin during foaming is improved, the foaming ratio can be increased, the closed-cell ratio of the foam beads improves, and the processability for molding into a molded article becomes excellent. Thus, adjusting the balance between flame retardancy and foamability is extremely important.

[0058] -Rubber components- The resin foam (A) is more preferably made to contain a rubber component in order to improve foaming properties.

[0059] The rubber components are not limited to but include, for example, butadiene, isoprene, and 1,3-pentadiene. These are preferably dispersed as particles in a continuous phase made of a polystyrene resin. As for how to add these rubber components, the rubber components themselves may be added, or resins such as styrene elastomers, styrene-butadiene copolymers, and high-impact polystyrene resins obtained by graft copolymerization of polybutadiene with polystyrene may be used as rubber component sources. In the latter case, the ratio (R) of the rubber components can be calculated using the following formula. R = C × Rs / 100 (C: Rubber concentration (mass%) in the rubber component source) Rs: Rubber source content in resin foam (A) (mass%)

[0060] When a rubber component is included, the rubber component content is preferably 0.3 to 10% by mass, more preferably 0.5 to 10% by mass, and even more preferably 1 to 8% by mass in the resin foam (A). When the rubber component content is 0.3% by mass or more, the desired flame retardancy is more easily achieved. Furthermore, when the rubber component content is 0.5% by mass or more, the flexibility and elongation of the resin (a) are excellent, the foam cell film is less likely to break during foaming, the foaming ratio is increased, and the foamed beads have excellent moldability even after foaming. When flame retardancy is important, it is preferable to add more polyphenylene ether resin and flame retardant, but both of these adversely affect foaming properties when their amounts are increased. In such compositions, a rubber component is suitable for imparting foaming properties. This is particularly important in bead foaming, where the temperature is gradually raised from room temperature and the resin is foamed in a non-molten state, and is a major difference from extrusion foaming, where the resin is foamed in a molten state. From the perspective of the degree of freedom in the shape of molded products, bead-formed foam products, which can be filled into a desired mold and molded, are more advantageous than extruded foam products that are extruded into a sheet shape. The fact that foam beads can achieve both flame retardancy and high foaming properties is extremely useful.

[0061] On the other hand, if the rubber component content is 10% by mass or less, the desired flame retardancy is more likely to be achieved. Furthermore, if the rubber component content is 8% by mass or less, sufficient heat resistance can be obtained. The shape of the rubber particles is not particularly limited; they may form a so-called salami structure in which multiple polystyrene resin fine particles are enclosed inside a particle with a rubber component as an outer shell, or they may form a so-called core-shell structure in which a single styrene resin fine particle is enclosed inside a particle with a rubber component as an outer shell. The rubber particle size of the rubber component is not particularly limited, but 0.5 to 5.0 μm is preferred for the salami structure, and 0.1 to 1.0 μm for the core-shell structure. Within this range, it is easier to exhibit better foaming properties.

[0062] -Styrene monomer content- From the viewpoint of foaming moldability, the resin foam (A) preferably contains styrene monomer units. The styrene monomer unit content is preferably in the range of 8% to 70% by mass, more preferably 10% to 68% by mass, even more preferably 12% to 66% by mass, even more preferably 14% to 64% by mass, and particularly preferably 16% to 62% by mass, relative to the total resin foam (A). In particular, by setting the styrene monomer content in the range of 14% to 64% by mass relative to the total resin foam (A), it becomes easier to obtain a resin foam (A) with a high closed-cell ratio and excellent heat insulation properties. The styrene monomer content in the resin foam (A) was measured by thermal decomposition GC / MS. Specifically, it was determined by the method described in the examples below.

[0063] -Other optional additives- The resin foam (A) may contain other optional additives besides the resin (a), flame retardant, and rubber component described above. Examples of other optional additives include mold release agents, antioxidants, heat stabilizers, lubricants, colorants (pigments, dyes), weather resistance modifiers, antistatic agents, impact modifiers, glass beads, inorganic fillers, and nucleating agents such as talc. These other optional additives can be added insofar as they do not impair the objectives of the present invention.

[0064] --Release agent-- In this embodiment, the release agent is an optional additive component of the resin foam (A). The release agent may be incorporated in the form of an internal humectant mixed into the resin before foaming, or in the case of a bead foam, it may be an external humectant that is dry-blended, or a combination of the two forms may be used.

[0065] The release agent content in this embodiment is preferably 0.001 to 2.0% by mass relative to the total amount (100% by mass) of the resin foam (A), with upper limits being 1.8% by mass or less, 1.7% by mass or less, 1.6% by mass or less, 1.5% by mass or less, 1.4% by mass or less, 1.3% by mass or less, 1.2% by mass or less, 1.1% by mass or less, 1.0% by mass or less, 0.9% by mass or less, 0.8% by mass or less, 0.7% by mass or less, and 0. The lower limit is most preferably 6% by mass or less, followed by 0.003% by mass or more, 0.005% by mass or more, 0.007% by mass or more, 0.009% by mass or more, 0.01% by mass or more, 0.012% by mass or more, 0.031% by mass or more, 0.066% by mass or more, 0.090% by mass or more, 0.11% by mass or more, 0.16% by mass or more, 0.21% by mass or more, 0.26% by mass or more, and 0.31% by mass or more. By setting the release agent content in the range of 0.001 to 2.0% by mass relative to the total amount (100% by mass) of the resin foam (A), a foam with excellent release properties can be obtained, which is particularly advantageous when forming a mold in the case of bead foaming. In particular, by setting the release agent content in the range of 0.01 to 0.8% by mass, a foam with an excellent balance of release properties and heat resistance can be obtained.

[0066] If the resin foam (A) of this embodiment contains a release agent as a humectant, the content of the humectant is preferably 0.05 to 2.0% by mass, more preferably 0.10 to 1.5% by mass, even more preferably 0.13 to 1.0% by mass, and still more preferably 0.17 to 0.8% by mass, based on the total amount (100% by mass) of the resin foam (A). In particular, by setting the content of the humectant in the range of 0.13 to 1.0% by mass, excessive bleed-out can be suppressed, and a resin foam (A) with excellent release properties can be obtained.

[0067] --Colorants-- The coloring agent in this embodiment is an optional additive and is used when it is necessary to color the resin foam (A). In particular, depending on the application, it is often colored black to make dirt less visible and for better identification. Coloring it black provides a desirable appearance and some resistance to heat and light. The coloring agent is not particularly limited, but carbon black, titanium dioxide, and organic dyes can be used. Examples of carbon black include those produced by the furnace process (furnace black), channel process (channel black), acetylene process (acetylene black), or thermal process (thermal black).

[0068] When coloring a resin foam (A) black with carbon black, the carbon black content in the resin foam (A) is preferably 0.05 to 5.0% by mass relative to the total amount (100% by mass) of the resin foam (A). If the carbon black content is less than 0.05% by mass, the desired blackness will not be achieved, and the foam will appear grayish. If it exceeds 5.0% by mass, there will be no change in the blackness. Therefore, from the viewpoint of cost and mechanical strength, it is preferable to have a carbon black content of 5.0% by mass or less. The method of adding the colorant is not particularly limited. It may be added after polymerization, directly blended during kneading, or added during kneading using a high-concentration masterbatch.

[0069] [Preferred composition of resin foam (A)] In one preferred embodiment, the resin foam (A) preferably contains a resin (a) obtained by mixing a polyphenylene ether resin and a polystyrene resin, a flame retardant, and a rubber component. In this case, the content of each component is preferably 40 to 94% by mass of the polyphenylene ether resin, 5 to 20% by mass of the flame retardant, and 0.3 to 10% by mass of the rubber component, with the remainder being the polystyrene resin. Furthermore, the content of styrene monomer units contained in the resin foam (A) is preferably in the range of 8% by mass or more and 70% by mass or less of the total resin foam (A). A thermal insulation material containing such a resin foam (A) can be made to be a thermal insulation material that is excellent in flame retardancy, heat resistance, and water resistance.

[0070] As described above, preferred compositions that can constitute the resin foam (A) of this embodiment include a resin (a) obtained by mixing a polyphenylene ether resin and a polystyrene resin, a flame retardant, and a rubber component. In this case, the total content of these components is preferably 65 to 100% by mass of the total resin foam (A), more preferably 75 to 99% by mass, even more preferably 80 to 98% by mass, even more preferably 85 to 97% by mass, particularly preferably 88 to 95% by mass, and most preferably 92 to 96% by mass.

[0071] The total content of the resin (a) obtained by mixing a polyphenylene ether resin and a polystyrene resin, a flame retardant, a rubber component, and other optional additives that can constitute the resin foam (A) of this embodiment is preferably 65 to 100% by mass of the total resin foam (A), more preferably 75 to 99% by mass, even more preferably 80 to 98% by mass, even more preferably 85 to 97% by mass, particularly preferably 88 to 95% by mass, and most preferably 92 to 96% by mass.

[0072] [Physical properties of resin foam (A)] Up to this point, we have described the composition of resin foam (A). Below, we will describe the physical properties of resin foam (A).

[0073] -Flame retardancy measured in accordance with UL standard UL-94 vertical method (20mm vertical combustion test)- The resin foam (A) has a flame retardancy of V-0 to V-2, as measured in accordance with the UL standard UL-94 vertical method (20mm vertical combustion test). When the resin foam (A) satisfies these physical properties, it becomes a highly flame-retardant thermal insulation material. From the viewpoint of even greater flame retardancy, it is preferable that the resin foam (A) has a flame retardancy of V-0 or V-1, as measured in accordance with the UL standard UL-94 vertical method (20mm vertical combustion test). To ensure that the resin foam (A) satisfies these physical properties, possible, but not limited to, methods include using a resin with excellent flame retardancy and adding a flame retardant.

[0074] -Water absorption rate- The resin foam (A) has a water absorption rate of 0.01 g / cm³ as measured in accordance with JIS K6767B. 2 The following is true: When the resin foam (A) satisfies these physical properties, it becomes a highly water-resistant insulating material. And because of its excellent water resistance, the insulating material can be applied to equipment where water is used. From the standpoint of excellent water resistance, the resin foam (A) has a water absorption rate of 0.005 g / cm³ as measured in accordance with JIS K6767B. 2 Preferably, it is 0.002 g / cm³. 2 It is more preferable that the following is the case: 0.0008 g / cm³ 2 It is even more preferable that the following is the case: 0.0005 g / cm³ 2 It is even more preferable that the following conditions are met. On the other hand, the water absorption rate is 0.00003 g / cm³. 2 The above is also acceptable. If the water absorption rate is above this lower limit, it will have sufficient water resistance. To ensure that the resin foam (A) satisfies these physical properties, some, though not limited to, methods include using a resin with low water absorption, or attaching or plating metal foil immediately after foam molding.

[0075] - Closed cell ratio - The closed-cell ratio of the resin foam (A) is preferable as it is higher, preferably 50% or more, more preferably 60% or more, even more preferably 70% or more, even more preferably 73% or more, even more preferably 76% or more, and even more preferably 79% or more. When the closed-cell ratio of the foam beads is 50% or more, the foam beads tend to have better moldability into foam beads, and when it is 70% or more, the heat insulation properties tend to be superior. The closed-cell ratio can be measured by the method described in the examples below.

[0076] -density- The density of the resin foam (A) is 0.01 to 0.80 g / cm³. 3 Preferably, it is 0.04 to 0.67 g / cm³. 3 It is more preferable that the concentration be 0.05 to 0.5 g / cm³.3 It is even more preferable that the concentration be 0.06-0.4 g / cm³. 3 It is even more preferable that the concentration be 0.07 to 0.3 g / cm³. 3 It is particularly preferable that the density of the resin foam (A) is 0.01 to 0.80 g / cm³. 3 This makes it easier to obtain foamed beads that are suitable for the secondary foaming process, especially when the concentration is 0.06~0.4 g / cm³. 3 By setting the range accordingly, it becomes even easier to satisfy the desired flame retardancy. The density of the resin foam (A) can be measured by the method described in the examples below.

[0077] - Dimensional change rate due to heating - The heating dimensional change rate of the resin foam (A) is not particularly limited, but at 100°C, it is preferably 2.0% or less, more preferably 1.7% or less, and even more preferably 1.4% or less. If the heating dimensional change rate is 2% or less, it has excellent heat resistance and can be used in environments where heat is used, such as washing machines and dryers.

[0078] [Method for manufacturing resin foam (A)] Next, we will explain the method for producing the resin foam (A).

[0079] The resin foam (A) can be obtained by impregnating a base resin with a foaming agent (impregnation step), forming foam beads by foaming (foaming step), filling a mold with the obtained foam beads, and foaming it (molding step).

[0080] In the impregnation process, the method for incorporating the foaming agent into the base resin is not particularly limited, and commonly used methods can be applied. Methods for incorporating the foaming agent include using an aqueous medium with a suspension system such as water (suspension impregnation), using a thermal decomposition type foaming agent such as sodium bicarbonate (foaming agent decomposition method), creating an atmosphere with gas above critical pressure and contacting the base resin in a liquid phase state (liquid phase impregnation), and contacting the base resin in a gas phase state under a high-pressure atmosphere below critical pressure (gas phase impregnation). Among these, gas phase impregnation under a high-pressure atmosphere below critical pressure is particularly preferred. Compared to suspension impregnation carried out under high-temperature conditions, gas phase impregnation offers better solubility of the gas in the resin, making it easier to increase the foaming agent content. This makes it easier to achieve a high foaming ratio and to create more uniform bubble sizes within the base resin. Similarly, the foaming agent decomposition method is carried out under high-temperature conditions, and not all of the added thermal decomposition type foaming agent turns into gas, resulting in a relatively smaller amount of gas generation. Therefore, gas-phase impregnation has the advantage of making it easier to achieve a higher foaming agent content. In addition, compared to liquid-phase impregnation, equipment such as pressure resistance devices and cooling devices can be made more compact, making it easier to keep equipment costs down.

[0081] The gas-phase impregnation conditions are not particularly limited, but an ambient pressure of 0.5 to 6.0 MPa is preferred. The ambient temperature is preferably 5 to 30°C, and more preferably 7 to 15°C. When the ambient pressure and temperature are within the above ranges, gas dissolution into the base resin proceeds more efficiently. In particular, if the ambient temperature is low, the amount of impregnation increases but the impregnation rate slows down, and if the ambient temperature is high, the amount of impregnation decreases but the impregnation rate speeds up. Therefore, it is preferable to set the ambient temperature as described above to efficiently promote gas dissolution into the base resin.

[0082] The blowing agent is not particularly limited, and commonly used gases can be used. Examples include inorganic gases such as air, carbon dioxide, nitrogen, oxygen, ammonia, hydrogen, argon, helium, and neon; fluorocarbons such as trichlorofluoromethane (R11), dichlorodifluoromethane (R12), chlorodifluoromethane (R22), tetrachlorodifluoroethane (R112), dichlorofluoroethane (R141b), chlorodifluoroethane (R142b), difluoroethane (R152a), HFC-245fa, HFC-236ea, HFC-245ca, and HFC-225ca; saturated hydrocarbons such as propane, n-butane, i-butane, n-pentane, i-pentane, and neopentane; dimethyl ether, diethyl ether, methyl ethyl ether, isopropyl ether, n-butyl ether, diisopropyl ether, furan, and fur. Examples include ethers such as rufural, 2-methylfuran, tetrahydrofuran, and tetrahydropyran; ketones such as dimethyl ketone, methyl ethyl ketone, diethyl ketone, methyl n-propyl ketone, methyl n-butyl ketone, methyl i-butyl ketone, methyl n-amyl ketone, methyl n-hexyl ketone, ethyl n-propyl ketone, and ethyl n-butyl ketone; alcohols such as methanol, ethanol, propyl alcohol, i-propyl alcohol, butyl alcohol, i-butyl alcohol, and t-butyl alcohol; carboxylic acid esters such as methyl formate, ethyl formate, propyl formate, butyl formate, amyl formate, methyl propionate, and ethyl propionate; and chlorinated hydrocarbons such as methyl chloride and ethyl chloride.

[0083] From the viewpoint of flame retardancy, the blowing agent is preferably non-flammable and non-combustible, and from the viewpoint of gas safety, an inorganic gas is more preferable. Furthermore, inorganic gases are less soluble in resin than organic gases such as hydrocarbons, and the gas escapes easily from the resin after the foaming and molding processes, which has the advantage of providing better dimensional stability of the molded product over time. In addition, plasticization of the resin due to residual gas is less likely to occur, and there is also the advantage that excellent heat resistance can be exhibited from an earlier stage after molding. Among inorganic gases, carbon dioxide is preferred from the viewpoint of solubility in resin and ease of handling, and its impregnation amount is preferably 3 to 13% by mass relative to the resin, and more preferably 3.5 to 10% by mass.

[0084] If the carbon dioxide impregnation amount is less than 3% by mass, it becomes difficult to achieve a higher foaming ratio, and the bubble size tends to vary, leading to greater variation in foaming ratios among the foam beads. If the carbon dioxide impregnation amount exceeds 13% by mass, the bubble size becomes smaller, and over-foaming tends to occur, making it difficult to maintain the closed-cell ratio.

[0085] The foaming method in the foaming process is not particularly limited, but examples include a method of rapidly releasing the material from high-pressure conditions to a low-pressure atmosphere to expand the gas dissolved in the base resin, or a method of heating the material with pressurized steam or the like to expand the gas dissolved in the base resin. Among these, the method of heating to foam is particularly preferred. This is because, compared to the method of rapidly releasing the material from high-pressure conditions to a low-pressure atmosphere, the size of the bubbles inside the foam beads tends to become more uniform. In addition, it has the advantage of making it easier to control the foaming ratio, especially for low-foaming ratio products.

[0086] Pressurized steam can be introduced, for example, from the bottom of the foaming furnace through numerous steam vents, and the resin can be stirred by a stirring blade to achieve more uniform and efficient foaming. The rotation speed of the stirring blade is preferably 20 to 120 rpm, and more preferably 50 to 90 rpm. If the rotation speed is less than 20 rpm, the pressurized steam will not be applied uniformly, making foaming control difficult and potentially leading to problems such as blocking. If the rotation speed exceeds 120 rpm, the beads during foaming will be damaged by the stirring blade, which tends to reduce the closed-cell ratio and prevent the desired foaming ratio from being achieved.

[0087] When foaming foam beads to a desired foaming ratio, the foaming process may be carried out in one stage, or in multiple stages, including secondary and tertiary foaming. When foaming in multiple stages, it is preferable to pressurize the reserve beads (beads that have not undergone the final foaming stage, etc.) with an inorganic gas before foaming in each stage. The gas used for pressurization is not particularly limited, but an inorganic gas is preferred from the viewpoint of flame retardancy and gas safety. Examples of inorganic gases include air, carbon dioxide, nitrogen, oxygen, ammonia, hydrogen, argon, helium, and neon. Carbon dioxide and air are preferred from the viewpoint of ease of handling and economic efficiency, but are not limited to these. The method of pressurization is also not particularly limited, but examples include filling a pressurized tank with reserve beads and supplying an inorganic gas to the tank to pressurize it.

[0088] To reduce the concentration of aliphatic hydrocarbon gases in the foamed beads to 1000 ppm or less, this can be achieved, for example, by using inorganic gases as foaming agents, or by performing a "maturation process" in which the foamed beads are left under high temperature conditions (for example, arbitrarily set between 40°C and 80°C) for a long period of time to release any remaining gases.

[0089] In the molding process, foam beads can be molded using general molding methods.

[0090] Examples of molding methods include, but are not limited to, a method in which foamed beads are filled into a mold, heated to cause foaming and simultaneous fusion of the beads, and then solidified by cooling. The method of filling the foamed beads is not particularly limited, but examples include the cracking method in which the mold is filled with the beads while slightly open, the compression method in which the beads are compressed under pressure and filled into the mold while the mold is closed, and the compression cracking method in which the beads are compressed and then cracked.

[0091] It is preferable to perform a pressurization process in which the foam beads are subjected to pressure treatment under an inorganic gas atmosphere before filling. This is because pressurization allows a constant gas pressure to be applied to the bubbles in the foam beads, making it easier to perform more uniform foam molding. The pressure source when performing pressurization is not particularly limited, but it is preferable to use an inorganic gas from the viewpoint of flame retardancy, heat resistance, and dimensional stability mentioned above. Examples of inorganic gases include air, carbon dioxide, nitrogen gas, oxygen gas, ammonia gas, hydrogen gas, argon gas, helium gas, neon gas, etc. Carbon dioxide and air are preferred from the viewpoint of ease of handling and economic efficiency, but are not limited to these. The method of pressurization is also not particularly limited, but examples include filling a pressurized tank with foam beads and supplying an inorganic gas to the tank to pressurize it.

[0092] By using foamed beads in the molding process, it becomes possible to manufacture molded bodies with fine or complex shapes using known in-mold molding methods, which broadens the range of applications.

[0093] For example, the foam beads can be molded using a vacuum molding method (e.g., Japanese Patent Publication No. 46-38359), in which a pair of molds for in-mold molding of conventional foam beads are used, the foam beads are filled into the mold cavity under pressurized atmospheric pressure or reduced pressure, the mold is closed to compress the volume of the mold cavity to a reduction of 0-70%, and then a heat transfer medium such as steam is supplied into the mold to heat and fuse the foam beads. Alternatively, the foam beads can be molded using a pressure molding method (e.g., Japanese Patent Publication No. 51-22951), in which the foam beads are pre-pressurized with pressurized gas to increase the pressure inside the foam beads and enhance their secondary foaming properties, and while maintaining these properties, the foam beads are filled into the mold cavity under atmospheric pressure or reduced pressure and the mold is closed, and then a heat transfer medium such as steam is supplied into the mold to heat and fuse the foam beads.

[0094] Furthermore, the foam beads can also be molded by a compression filling molding method (Japanese Patent Publication No. 4-46217), in which foam beads pressurized to a pressure exceeding atmospheric pressure are filled into a cavity pressurized to a pressure exceeding atmospheric pressure using compressed gas, and then a heat transfer medium such as steam is supplied into the cavity to heat and fuse the foam beads. In addition, foam beads with high secondary foaming strength obtained under special conditions can also be molded by an atmospheric pressure filling molding method (Japanese Patent Publication No. 6-49795), in which foam beads with high secondary foaming strength obtained under special conditions are filled into a pair of mold cavities under atmospheric pressure or reduced pressure, and then a heat transfer medium such as steam is supplied to heat and fuse the foam beads, or by a method combining the above methods (Japanese Patent Publication No. 6-22919).

[0095] (Other foams besides resin foam (A)) The thermal insulation material of this embodiment may consist of one type of foam or two or more types of foam. Specifically, the thermal insulation material may consist of resin foam (A), or it may consist of resin foam (A) and one or more other types of foam other than resin foam (A) (hereinafter, other foams other than resin foam (A) may simply be referred to as "other foams"). Examples of foams other than resin foam (A) include non-flammable foam, non-water-resistant foam, and non-heat-resistant foam. By using other foams in addition to resin foam (A), cost reductions can be expected, for example. For example, non-flammable foam may be used in parts where flame retardancy is not required, and resin foam (A) may be used in parts where flame retardancy is required. Preferably, the thermal insulation material of this embodiment includes, in addition to the resin foam (A), a non-flammable resin foam (B) (hereinafter also simply referred to as "foam (B)"), which will be described later.

[0096] When the thermal insulation material of this embodiment includes a resin foam (A) and other foams, the composition of the resin foam (A) and other foams is not particularly limited and can be configured according to the desired effect. In one embodiment, since the resin foam (A) and the other foams are each composed of a part of the thermal insulation material according to the required and unnecessary properties, it is preferable that the laminated structure is not designed in such a way that these two types of foams work together as a single unit.

[0097] Furthermore, although not limited thereto, for example, the volume ratio of resin foam (A) to other foams in the thermal insulation material is preferably 9:1 to 1:9. More preferably, the volume ratio of resin foam (A) to other foams (resin foam (A): other foams) is in the range of 8:2 to 2:8, and even more preferably 7:3 to 3:7.

[0098] [Foam (B)] The foam (B) is not particularly limited as long as it is a non-flammable foam. In this specification, "non-flammable" means that the flame retardancy measured in accordance with the UL standard UL-94 vertical method (20 mm vertical combustion test) does not meet the V-0 to V-2 criteria. The foam (B) contains resin (b).

[0099] The resin constituting resin (b) can be a thermoplastic resin or a thermosetting resin, but from the viewpoint of productivity and recyclability, a thermoplastic resin is preferred. Specifically, examples of thermoplastic resins include, but are not limited to, polyolefin resins such as polyethylene resins and polypropylene resins, polystyrene resins, heat-resistant polystyrene resins, modified polyphenylene ether resins, polyethylene terephthalate (PET) resins, polyamide (nylon) resins, polycarbonate resins, and thermosetting resins such as melamine resins and phenolic resins. Furthermore, these can be used individually or in combination of two or more. Of these, polyolefin resins, polystyrene resins, or modified polyphenylene ether resins are preferred from the viewpoint of processability and performance.

[0100] In addition to resin (b), foam (B) may also contain other thermoplastic resins, antioxidants, heat stabilizers, lubricants, pigments, dyes, weathering modifiers, impact modifiers, glass beads, inorganic fillers, and nucleating agents such as talc, as described above for resin foam (A), to the extent that they do not impair the purpose of the invention.

[0101] The foaming ratio of foam (B) is not particularly limited, but is preferably in the range of 1.5 to 100 cc / g, more preferably 2 to 60 cc / g, even more preferably 3 to 50 cc / g, still more preferably 5 to 50 cc / g, still more preferably 6 to 40 cc / g, still more preferably 7 to 30 cc / g, and still more preferably 8 to 20 cc / g. When the foaming ratio is in the range of 1.5 to 100 cc / g, it tends to be easier to maintain excellent flame retardancy while taking advantage of the benefits of weight reduction.

[0102] The heating dimensional change rate of the foam (B) is not particularly limited, but is preferably 10% or less, more preferably 5% or less, and even more preferably 3% or less at 100°C. A heating dimensional change rate of 10% or less provides excellent heat resistance, making it applicable to components used in high-temperature environments, and furthermore, allowing for long-term storage in high-temperature environments during the summer.

[0103] The heat deflection temperature (HDT) of the foam (B) is not particularly limited, but is preferably 60°C or higher, and more preferably 70°C or higher. When the heat deflection temperature is 60°C or higher, it exhibits excellent heat resistance, and the same effects as described above can be obtained.

[0104] (Physical properties of thermal insulation materials) -Thermal conductivity- The thermal conductivity of the insulating material in this embodiment is not particularly limited, but is preferably 0.020 to 0.060 W / (m·K), more preferably 0.025 to 0.050 W / (m·K), and even more preferably 0.030 to 0.045 W / (m·K). When the thermal conductivity is 0.020 to 0.060 W / (m·K), the insulating performance of the insulating material becomes even better.

[0105] (Method of manufacturing insulation material) The thermal insulation material of this embodiment can be manufactured, for example, by the method for manufacturing the resin foam (A) described above, if the thermal insulation material consists of a resin foam (A). Furthermore, if the thermal insulation material includes other foams such as foam (B) in addition to the resin foam (A), the foams can be manufactured separately and then joined together by methods such as adhesive bonding, mechanical bonding, or heat fusion. Alternatively, the resin foam (A) and the other foams may be used without joining them, as long as their function is maintained. The above methods are examples of how foams can be joined together, but they are not limited to these.

[0106] The adhesive used to bond foams together is not particularly limited as long as it is capable of bonding resins together or resins together with inorganic materials. For example, acrylic, epoxy, or vinyl acetate adhesives can be used.

[0107] Heat fusion is preferable when the resin used in the foamed resin and the resin used in the resin foam (A) are resins that have good adhesion to each other. Specifically, the other foam and the resin foam (A) can be melted to a degree that allows for fusion, and then brought into contact with each other for bonding. Furthermore, even when the resins do not have very good adhesion to each other, it is possible to bond the other foam and the resin foam (A) more strongly by using an anchoring effect such as corona treatment. It is also possible to bond more strongly by roughening the surface of the foamed molded product by physical cutting or other processes.

[0108] This disclosure also relates to an apparatus for drying moisture-containing clothing, which incorporates the insulating material of this embodiment. The above-mentioned device for drying clothes containing moisture is equipped with the aforementioned insulating material, which makes it difficult for the heat used for drying to escape. As a result, it is thought that drying time can be shortened, energy consumption can be reduced, electricity costs can be lowered, and CO2 emissions can be suppressed.

[0109] Equipment for drying clothes containing moisture includes washer-dryers and dryers. Furthermore, washer-dryers include drum-type washer-dryers and top-loading washer-dryers. The washing machine and dryer mentioned above may be conventionally known models.

[0110] In the above-mentioned apparatus for drying clothes containing moisture, the shape and area in which the insulating material is placed are not particularly limited and can be appropriately selected depending on the apparatus in which the insulating material is placed. For example, in the case of a drum-type washer-dryer, the area in which the insulating material is placed may be part or all of the gap between the drum and the casing, and the area around the drum. The shape of the insulating material can also be selected to match the shape of the area in which it is placed. Examples of insulating material shapes include cylindrical, rectangular parallelepiped, or rectangular parallelepiped with a curved recess formed on at least one surface.

[0111] The number of insulating materials used in a device for drying clothes containing moisture is not particularly limited. For example, the number of insulating materials in a device for drying clothes containing moisture may be one or two or more. The number of insulating materials refers to the number of insulating materials as a single, unseparated mass.

[0112] The method for manufacturing the apparatus for drying clothes containing moisture according to this embodiment is not particularly limited. For example, the apparatus for drying clothes containing moisture according to this embodiment may be manufactured by first manufacturing the apparatus using a method for manufacturing an apparatus for drying clothes containing moisture, such as a washing machine or dryer, and then removing a part of the exterior of the casing and placing insulating material in any part, or the insulating material may be placed in any part during the manufacturing process of the apparatus. [Examples]

[0113] The present disclosure will be further described below with reference to examples, but the present disclosure is not limited in any way to the examples described below.

[0114] <Evaluation Method> The evaluation methods used in the examples and comparative examples are described below.

[0115] (density) After measuring the weight W (g) of the foam, the volume V (cm³) was measured using the immersion method. 3 ) is measured and its weight is divided by its volume to obtain the value W / V (g / cm³). 3 ) was defined as the density.

[0116] (Expansion ratio) After measuring the weight W (g) of the foam, its volume V (cc) was measured using the immersion method, and the value V / W (cc / g), obtained by dividing the volume by the weight, was defined as the foaming ratio.

[0117] (Percentage of closed cells) The true volume (Vx) of a foam with a known expansion ratio (cc / g) was measured using an air-comparison hydrometer manufactured by Beckmann, Inc., and the closed-cell ratio: S (%) was calculated using the following formula.

number

[0118] (Flame retardant) The flame retardancy was evaluated by conducting tests in accordance with the UL-94 vertical method (20mm vertical combustion test) of the US UL standard. The measurement method is shown below. The foam was molded into test specimens measuring 125 mm in length, 13 mm in width, and 3 mm in thickness, and five of these molded specimens were used for evaluation. The test specimens were mounted vertically on clamps, and two 10-second indirect flame tests were performed using a 20 mm flame. Based on the combustion behavior, a rating of V-0, V-1, V-2, or non-conforming was determined. Any specimens that did not meet the following criteria were deemed non-conforming. V-0: In both the first and second trials, the duration of flamed combustion was within 10 seconds. Furthermore, the sum of the duration of flamed combustion and flameless combustion in the second trial was within 30 seconds. Additionally, the sum of the flamed combustion times of the five test specimens was within 50 seconds. No samples burned up to the position of the fixing clamp, and there was no cotton ignition by burning debris. V-1: In both the first and second trials, the duration of flamed combustion was within 30 seconds. Furthermore, the sum of the duration of flamed and flameless combustion in the second trial was within 60 seconds. Additionally, the sum of the flamed combustion times of the five test specimens was within 250 seconds. No samples burned up to the position of the fixing clamp, and there was no cotton ignition by burning debris. V-2: In both the first and second trials, the duration of flamed combustion was within 30 seconds. Furthermore, the sum of the duration of flamed and flameless combustion in the second trial was within 60 seconds. Additionally, the sum of the duration of flamed combustion for all five test specimens was within 250 seconds. No samples burned up to the position of the fixing clamp. Cotton ignition occurred due to falling combustion material.

[0119] (Water absorption rate) The foam prepared using the method described below was cut into 100mm x 100mm squares, and its water absorption rate was measured in accordance with JIS K6767B. Since the evaluation was performed on skinned samples, the unit of water absorption rate is g / cm³. 2That's what I decided.

[0120] (Glass transition temperature) Dynamic viscoelasticity measurements were performed on the resin contained in the foam using a rheometer (Anton Paar "Physica MCR301") under the following conditions, and the low-temperature half-width (°C) of the loss tangent (tanδ) was determined. At this time, the peak temperature (°C) of the loss tangent (tanδ) was defined as the glass transition temperature (Tg) of the base resin composition. Measuring jig: SRF10 Measurement mode: vibration φ, γ Strain: Swing angle γ = 0.015% Frequency: 1Hz Measurement temperature: 20℃~200℃ Heating rate: 2°C / min Normal force: -0.3N Measurement points: 180 Time unit: s

[0121] (Content of styrene monomer units and rubber components) The content of styrene monomer units and rubber components in the foam was measured by thermal decomposition GC / MS under the following conditions, using the resins and foams prepared in the examples and comparative examples. Quantitative values ​​were obtained using a calibration curve method with standard samples whose monomer content was known. <<Sample Preparation>> Weigh 20 μg of the resin or composition prepared in the examples and comparative examples into a sample cup using a precision balance. <<Measurement Conditions>> <Pyrolysis Unit> Equipment: Frontier Lab PY-3030D Furnace temperature: 600℃ <GC / MSユニット> Equipment: Shimadzu Corporation GCMS-GP2020NX Column: Ultra Alloy-5 (Length 30m, film thickness 0.25μm, diameter 0.250mmφ) Column temperature: The column was held at 50°C for 5 minutes, then the temperature was increased at a rate of 10°C / min, and from 100°C onwards, the temperature was increased at a rate of 7°C / min, and it was held at 300°C for 10 minutes. Inlet temperature: 300℃ Detector temperature: 300℃ Split ratio: 1 / 300 Carrier gas: Helium Detection device: Mass spectrometer (MSD) Detection conditions: Scan mode or SIM mode (when there is an overlap between unwanted peaks and peaks that need detection) Furthermore, when detecting each monomer peak, the sample volume, the column used, and the heating rate were adjusted as appropriate to avoid peak intensity saturation and overlap between peaks to be detected.

[0122] (Cycle time for manufacturing insulation materials) The time taken from the molding process of each insulation material to the installation process as a component was measured and evaluated according to the following criteria. More specifically, the time taken to mold the insulation material using the method described in the example below and to install it on a cylindrical mounting section with an outer diameter of 530 mm and a depth of 350 mm was measured. A: Within 15 minutes B: More than 15 minutes but less than 20 minutes C: More than 20 minutes

[0123] (Parts cost) The component costs of each insulation material were evaluated according to the following criteria. A: The energy-saving effect as an insulating material can be recovered within 5 years. B: It takes more than 5 years to recoup the energy-saving effect as an insulating material.

[0124] (Suitability for use in washer-dryers) The following evaluation criteria were used to assess whether the product could be applied to a washer-dryer. Suitable: Flame retardancy is V-0 to V-2 (reaching V-2), and water absorption rate is 0.01 g / cm³. 2 The following conditions apply, and the glass transition temperature is 90°C or higher. Unacceptable: Does not meet the criteria for "acceptable".

[0125] <Example 1> 58% by mass of polyphenylene ether resin (PPE) (S201A, manufactured by Asahi Kasei Chemicals Corporation), 17% by mass of bisphenol A-bis(diphenyl phosphate) (BBP) as a phosphorus-based flame retardant, and 15% by mass of high-impact polystyrene resin (HIPS) with a rubber concentration of 6% by mass and 10% by mass of polystyrene (GPPS, grade: 685, manufactured by PS Japan Co., Ltd.) were added so that the rubber component content was 2.3% by mass. After heating, melting, and kneading in an extruder, the mixture was extruded to produce resin pellets. Following the method described in Example 1 of Japanese Patent Publication No. 4-372630, the resin pellets were placed in a pressure-resistant container, the gas in the container was replaced with dry air, and carbon dioxide (gas) was injected as a blowing agent. Under conditions of a pressure of 3.2 MPa and a temperature of 11°C, the resin pellets were impregnated with 7% by weight of carbon dioxide over 3 hours. The resin pellets were then foamed in a foaming furnace with pressurized steam while rotating a stirring blade at 77 rpm to obtain foamed beads. The residual concentration of aliphatic hydrocarbon gas in these foamed beads was measured immediately after foaming, and it was below the detection limit (50 ppm). These foamed beads were pressurized to 0.5 MPa over 1 hour, and then held at 0.5 MPa for 8 hours to perform a pressurized treatment. This was then filled into an in-mold molding die with steam vents, heated with pressurized steam to expand and fuse the foamed beads together, cooled, and removed from the molding die to produce a resin foam (insulating material). The insulation material was evaluated using the method described above.

[0126] <Examples 2-4> As shown in Table 1, the thermal insulation materials for each example were prepared using the same method as in Example 1, except that the magnification ratio and composition of resin foam A were changed, and evaluated using the method described above.

[0127] <Example 5> An insulating material was prepared in the same manner as in Example 1, except that the molding method and composition were as shown in Table 1. Resin foam A was manufactured by extrusion foaming, and the extruded foam was cut to form the shape of an insulating material for a washing machine, which was then evaluated. While a material exhibiting similar performance as an insulating material was produced, the cutting process increased the cycle time of the component.

[0128] <Examples 6-11> In addition to flame-retardant resin foam A, a non-flammable resin foam B was also used to create the washing machine insulation material. By using resin foam B in the parts where flame retardancy was not required, the cost of the insulation component could be reduced. The resin foam B was prepared as follows. Polystyrene (GPPS, grade: 680, manufactured by PS Japan Co., Ltd.) was used as resin (b), and resin pellets were produced by extruding after heating, melting, and kneading in an extruder. Following the method described in Example 1 of Japanese Patent Publication No. 4-372630, the resin pellets were placed in a pressure vessel, the gas in the vessel was replaced with dry air, and carbon dioxide (gas) was injected as a blowing agent. Under conditions of a pressure of 3.2 MPa and a temperature of 11°C, the resin pellets were impregnated with 7% by weight of carbon dioxide over 3 hours. The resin pellets were then foamed in a foaming furnace with pressurized steam while rotating a stirring blade at 77 rpm to obtain foamed beads. The residual concentration of aliphatic hydrocarbon gas in these foamed beads was measured immediately after foaming, and was below the detection limit (50 ppm). These foamed beads were pressurized to 0.5 MPa over 1 hour, and then held at 0.5 MPa for 8 hours to perform a pressurized treatment. This was filled into an in-mold molding die having steam vents, heated with pressurized steam to expand and fuse the foam beads together, then cooled and removed from the molding die to produce resin foam B. Then, the prepared resin foam A and resin foam B were joined together so that they interlocked. At this time, the volume ratio of resin foam A to resin foam B (resin foam A:resin foam B) was as shown in Table 1 or Table 2.

[0129] <Examples 12-13> An insulating material was prepared in the same manner as in Examples 6 to 11, except that polyphenylene ether resin (PPE) (S201A, manufactured by Asahi Kasei Chemicals Corporation) was used in the composition ratio shown in Table 2, in addition to polystyrene (GPPS, grade: 685, manufactured by PS Japan Co., Ltd.) as the resin (b) constituting resin foam B.

[0130] <Example 14> An insulating material was prepared in the same manner as in Examples 6 to 11, except that polypropylene (manufactured by Prime Polymer Co., Ltd.) was used as the resin (b) constituting the resin foam B.

[0131] <Example 15> An insulating material was prepared in the same manner as in Examples 6 to 11, except that a styrene-methacrylic acid random copolymer (styrene:methacrylic acid = 96:4 (mass ratio)) was used as the resin (b) constituting the resin foam B.

[0132] <Comparative Example 1> An insulating material was prepared in the same manner as in Example 1, except that the resin component of resin foam A was made solely from polystyrene (GPPS, grade: 685, manufactured by PS Japan Co., Ltd.). The fabricated insulation material was evaluated using the method described above.

[0133] <Comparative Example 2> An insulating material was prepared in the same manner as in Example 1, except that the resin component of resin foam A was made solely from polypropylene (manufactured by Prime Polymer Co., Ltd.). The fabricated insulation material was evaluated using the method described above.

[0134] The evaluation results are shown in Tables 1 and 2.

[0135] [Table 1]

[0136] [Table 2]

[0137] Tables 1 and 2 show that the thermal insulation material of the example can be applied to clothes drying equipment such as washing machines and dryers, which require flame retardancy, heat resistance, and water resistance. [Industrial applicability]

[0138] According to this disclosure, it is possible to provide an insulating material that can be applied to clothing drying devices such as washing machines and dryers.

Claims

1. The resin foam (A) contains resin (a), The aforementioned resin foam (A) has a flame retardancy of V-0 to V-2 as measured in accordance with the UL standard UL-94 vertical method (20 mm vertical combustion test). The aforementioned resin foam (A) has a water absorption rate of 0.01 g / cm³ as measured in accordance with JIS K6767B. 2 The following: The glass transition temperature of the resin (a) contained in the resin foam (A) is 90°C or higher. An insulating material used in devices for drying clothes that contain moisture.

2. The thermal insulation material according to claim 1, wherein the resin foam (A) includes bead foam.

3. The thermal insulation material according to claim 1, wherein the resin foam (A) has a closed-cell ratio of 75% or more.

4. The resin foam (A) has a density of 0.01 g / cm³. 3 0.400g / cm or more 3 The thermal insulation material according to claim 1, which is as follows:

5. Furthermore, the thermal insulation material according to claim 1, further comprising a non-flammable foam (B).

6. The resin (a) contained in the resin foam (A) includes a polystyrene-based resin, The thermal insulation material according to claim 1, wherein the content of styrene monomer units is 8.0% by mass or more and 70.0% by mass or less in the resin foam (A).

7. The insulating material according to claim 1, wherein the device for drying the aforementioned moisture-containing clothing is a drum-type washing machine and dryer.

8. The thermal insulation material according to claim 1, wherein the resin (a) contained in the resin foam (A) includes a polyphenylene ether resin.

9. An apparatus for drying clothes containing moisture, comprising the insulating material described in claim 1.

Citation Information

Patent Citations

  • Foamed plastic-based heat insulation material

    JP2010110978A